1997
DOI: 10.1901/jeab.1997.68-143
|View full text |Cite
|
Sign up to set email alerts
|

Incongruous Stimulus Pairing and Conditional Discrimination Training: Effects on Relational Responding

Abstract: In Experiment 1, 5 subjects were exposed to a stimulus‐pairing procedure in which two nonsense syllables, identified by a letter‐number code as A1 and C2, each predicted the onset of a sexual film clip, and the nonsense syllables A2 and C1 each predicted the onset of a nonsexual film clip. Subjects were then exposed to a matching‐to‐sample test in which the nonsense syllables A1 and A2 were presented as sample stimuli and C1 and C2 were presented as comparison stimuli and vice versa (i.e., C stimuli as samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
2
25
1
1
Order By: Relevance
“…Consideration of this issue may also provide some insights into performances during probe phases. Specifically, the current experimental preparations bear some functional similarity to preparations used to examine the effect of established functional classes on the emergence or reorganization of stimulus equivalence classes, and vice versa (e.g., Roche, Barnes, & Smeets, 1997;Tyndall, Roche, & James, 2004, Wirth & Chase, 2002. Such studies have generally found that incongruous relations between functional and stimulus equivalence classes lead to the delayed emergence or disruption of one or the other.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of this issue may also provide some insights into performances during probe phases. Specifically, the current experimental preparations bear some functional similarity to preparations used to examine the effect of established functional classes on the emergence or reorganization of stimulus equivalence classes, and vice versa (e.g., Roche, Barnes, & Smeets, 1997;Tyndall, Roche, & James, 2004, Wirth & Chase, 2002. Such studies have generally found that incongruous relations between functional and stimulus equivalence classes lead to the delayed emergence or disruption of one or the other.…”
Section: Discussionmentioning
confidence: 99%
“…For example a subject may be required to produce 6 out of 6 correct responses in a row, before progressing to the testing phase (e.g., Dymond & Barnes, 1994). Other studies have required subjects to produce 8 out of 8 correct responses in a row (Healy, Barnes, & Smeets, 1998;Roche, Barnes, & Smeets, 1997) or 15 correct responses in a row (Wulfert, Dougher, & Greenway, 1991). In this experiment subjects were required to produce 12 out of 12 correct responses in a row before progressing to the testing phase.…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, a number of researchers have used equivalence phenomena to develop a behavior analytic interpretation of symbolic meaning and the generative nature of grammar (Barnes & Holmes, 1991; Hayes, Hayes & Hayes, 1989;Wulfert & Hayes, 1988). Finally, recent findings have shown that equivalence is important to a behavioral analysis of many disparate areas of research, such as social categorization (Grey & Barnes, 1996;Kohlenberg, Hayes, & Hayes, 1991;), human sexual behavior (Roche, Barnes, & Smeets, 1997;Roche, BarnesHolmes, Smeets, Barnes-Holmes, & McGeady, 2000), as well as the advanced reasoning abilities of humans (Hayes, Gifford, & Townsend, 2001;Lipkens, 1992).…”
mentioning
confidence: 99%